Pemanfaatan Teknologi untuk Meningkatkan Numerasi Peserta Didik SMP N 1 Kertanegara - Waluyo, Retno; Kusuma, Rahayu Linda; Zamora, Hanenda Putri (Jurnal Pengabdian Masyarakat (ABDIRA), 2024)
Numeracy is very important for junior high school students to learn because it has a significant impact on daily life such as problem solving abilities, critical thinking abilities and the ability to apply mathematical concepts in various situations. The numeracy ability index at junior high school level in Purbalingga Regency is rated "below minimum competency" with a score of 1.73 (scale 1-3). Problems among students at SMP N 1 Kertaengara related to numeracy include students having difficulty understanding basic mathematical concepts and more complex mathematical concepts. Another problem is that the numeracy teaching methods used by teachers are still monotonous and do not use technology. Therefore, efforts are needed to increase student numeracy, one of the efforts that can be made by utilizing technology. This activity aims to improve understanding of numeracy by utilizing technology so that students' numeracy skills increase. There are 3 stages of training starting from preparation, implementation and evaluation. The results of this activity can improve numeracy skills in a more effective and enjoyable way by utilizing technology in learning.